2016
DOI: 10.1002/psp.2023
|View full text |Cite
|
Sign up to set email alerts
|

Power Through Problem Solving: Latino Immigrants and the Inconsistencies of Economic Restructuring

Abstract: Employment restructuring is a transformative process that brings about significant changes in how work is organised and experienced. Scholars who study restructuring in industries that employ large numbers of immigrant workers, including construction, food processing, or janitorial services, often point to the undermining effects of this transformation on industry wage standards, working conditions, and training supports. But often missing from these accounts is a recognition that restructuring is uneven and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… Lowe and Iskander (, p. 2) question the type of transformation narrative presented here, focusing instead on the unevenness of workforce‐system change within the US construction sector: “employment restructuring is less a wholesale replacement of one set of practices (and people) with another. Rather, it unfolds unevenly as a work in progress—one that is shaped and even contested by the various industry actors … that encounter and enact restructuring in their daily work life.” This point is well taken.…”
mentioning
confidence: 99%
“… Lowe and Iskander (, p. 2) question the type of transformation narrative presented here, focusing instead on the unevenness of workforce‐system change within the US construction sector: “employment restructuring is less a wholesale replacement of one set of practices (and people) with another. Rather, it unfolds unevenly as a work in progress—one that is shaped and even contested by the various industry actors … that encounter and enact restructuring in their daily work life.” This point is well taken.…”
mentioning
confidence: 99%
“…Informality in domestic work is therefore built on different premises than informality in the business world, in which profit maximizing provides the main basis for labor relations. So instead of approaching the analysis from the outside looking in (i.e., how households applied or bypassed legal labor norms), we look inside out focusing on the microstructures of control and cooperation shaping employer–domestic employee everyday interactions (re)producing informality (Lowe & Iskander, this issue). To do so, we use an economic‐sociological lens.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown how migrants employed in the informal economy in the global north have sought to develop informal strategies of labour market and workplace regulation that create work structures and routines that effectively support skill development, knowledge sharing, and the promotion of quality work standards in sectors of the labour market where informalisation is high (Martin, ; Visser & Cordero‐Guzman, ; Melendez et al , , ). As Lowe and Iskander () and Guarnizo () show in their contributions, such strategies have the capacity to shape pathways migrant workers utilise to experience economic mobility and challenge workplace standards that counter the dominant perspective that informalisation serves as a mechanism for employers to exert greater control and discipline over migrant workers. Such strategies can, at times, tether migrant workers and employers together in ways that create a form of interdependency and internal mechanisms that have the potential to improve worker rights and mobility (for both migrant and “native” born workers) in the informal economy.…”
Section: Making Room For Manoeuvre: the State Market And Social Promentioning
confidence: 99%
“…Scott () articulates how the use of informal employment practices by employers in low‐wage sectors of the labour market contributes to the embedding of migrants in informal employment, but this process is driven by demand‐side factors that are shaped by capital interests in the context of the specific developmental ethos of the nation state. Lowe and Iskander () identify and analyse informal strategies by workers and employers in the construction industry that depart from institutionally prescribed and sanctioned mechanisms. They show how these informal practices help promote occupational mobility for migrants within the informal economy, while countering the dominant perception of the relationship between migrant workers and employers as one of exploitation and marginalisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation